Rural Education and Teacher Training - Gustavo Cunha de Araújo; Cicero da Silva (Universidade Federal do Norte do Tocantins, 2018)
The Brazilian Scientific Journal of Rural Education (Revista Brasileira de Educação do Campo), ISSN 2525-4863, a journal of the Rural Education course, Federal University of Tocantins, Campus of Tocantinópolis, Brazil, launches its third issue of volume 3, referring to the third quarter of 2018. This In the year 2018, in order to increase the quality of the editorial processes, as well as in the indexations and articles published in the journal, we had a significant achievement: the journal was accepted for indexing in the Emergin Sources Citation Index, Clarivate Analytics (Web of Science) database collection. It is an extremely important foundation, because through it, the magazine will have greater international visibility and will be evaluated to integrate other bases of this collection (Web of Science), so that Clarivate Analytics can grant us the impact factor. With the publication of this edition, which brings a great diversity of articles from different Brazilian and foreign institutions, journal ends 2018 even stronger. Of course, this is the result of the serious work of the editorial team and the trust that the different authors put in this journal to publish the results of their research. Therefore, with the growth of the RBEC the Field Education gains greater visibility and space in society in general, corroborating the mission of this journal. We wish you all a good read and a prosperous year of 2019!